Othering and Selfing: Reading Gender Hierarchies and Social Categories in Michel Houellebecq's Novel Soumission - Wening Udasmoro (Humaniora, 2018)
In literature, questions of the self and the other are frequently presented. The identity politics that gained prominence after the attack on the World Trade Center in New York on 11 September 2001 has occupied considerable space in this debate throughout the globe, including in France. One example of a novel dealing with the self and other is Michel Houellebecq’s Soumission (2015). This article attempts to explore the processes of selfing and othering in this work. The politics of identity that seems to present Muslims and Islam as the other and French as the self is also extended to other identities and aspects involved in the novel. This article attempts to show, first, how the French author Houellebecq positions the self and other in Soumission; second, the type of self and other the novel focuses on; and third, how its selfing and othering processes reveal the gender hierarchy and social categorization of French society. It finds that the novel presents a hierarchy in its narrative through which characters are positioned based on their gender and sexual orientation, as well as their age and ethnic heritage.